More Than a Ban on Smoking? Behavioural Spillovers of Smoking Bans in the Workplace - Joan Costa-Font; Luca Salmasi; Sarah Zaccagni (Institute of Labor Economics (IZA), 2021)
Are workplace smoking bans (WSBs) more than a ban on smoking? We study whether WSBs influence smoking cessation and exert behavioural spillover effects on (i) a number of health behaviours, and (ii) on individuals not directly affected by the bans. Drawing upon quasi-experimental evidence from Russia (a country where about half of the population smokes), which introduced a WBS (in addition to a smoking ban on public places), and adopting a difference-in-differences (DiD) strategy, which compares employed individuals (exposed to the work and public place ban) to those unemployed (exposed only to the ban in public places), we document three sets of findings. First, unlike previous studies (focusing on smoking bans in public places), we find robust evidence that WSBs increase smoking cessation in 2.9 percentage points (pp) among men. Second, we find that upon the WSB, quitters are less likely to use alcohol (6.7pp reduction among men and 3.5 pp among women), reduce their alcohol consumption (10 percent among men) and increase their physical activity (in 4.3 percentage points among men). WSBs are found to influence health behaviours of those not directly affected by the reform, such as never smokers. Our findings are consistent with a model of joint formation of health behaviours, and suggest of the needs to account for a wider set of spillover effects when estimating the welfare effect of WSBs.
Keywords: I18; H75; L51; 330; joint behavioural formation; workplace smoking bans; behavioural spillovers; smoking; drinking; physical activity; healthy identity; Russia